Gender-based interactional dynamics in EFL speaking anxiety: A mixed-methods study of lecturer interventions in vocational higher education - Annisa Romadloni; Laura Sari; Linda Perdana Wanti; Abdul Karim (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2026)
Speaking anxiety in English as a Foreign Language (EFL) classrooms limits students’ participation and oral proficiency, particularly in polytechnic English for Specific Purposes (ESP) contexts where communicative competence is closely linked to work readiness. This study aims to analyze gender differences in speaking anxiety and group preferences, the relationship between discomfort when speaking before the opposite gender and total anxiety, and lecturer interventions perceived as effective based on students’ gender. The study employed a convergent mixed methods design by integrating a questionnaire adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) and open-ended questions. Quantitative analysis included Welch’s independent samples t-test, chi-square test, and Pearson correlation, while qualitative analysis used inductive thematic coding with meta-inference at the integration stage. The findings indicate a moderate but statistically significant gender difference, with female students reporting higher levels of anxiety than male students. However, gender was not significantly associated with group preference. Anxiety was triggered by negative evaluation, mistakes, self-monitoring, and concerns about credibility, whereas group preference was shaped primarily by familiarity. Therefore, lecturer interventions should be adaptive: female students require a supportive learning atmosphere and linguistic scaffolding, while male students need sufficient preparation time and gradual participation. The study concludes that EFL speaking anxiety in vocational higher education is not determined solely by gender, but more dominantly by social mechanisms, fear of evaluation, ridicule, loss of credibility, and familiarity within classroom interaction. The study recommends normalizing mistakes, providing protected preparation time, prioritizing constructive feedback, expanding voluntary participation, and conducting longitudinal replications across institutions.